Bacterial Biofilm Inhibition and Antifungal Activity of Neotropical Plants - Ta, Chieu Anh Kim (Université d'Ottawa / University of Ottawa, 2015)
This thesis examined the antimicrobial activity of select neotropical plants from Costa Rica and traditional Q’eqchi Maya medicines from Belize. In particular the potential for interference with bacterial quorum sensing (QS) and biofilm formation as well as fungal growth were assessed. Of one hundred and twenty six extracts collected from Costa Rica, one third showed significant QS inhibition while 13 species displayed more biofilm inhibitory activities than the positive control allicin. The active species belonged to the Lepidobotryaceae, Melastomataceae, Meliaceae, Sapindaceae, and Simaroubaceae. Twelve Marcgraviaceae species were tested for the same biological activities; of these, three showed similar QS inhibition to that of the positive control Delisea pulchra (Greville) Montagne and five with at least 30% biofilm inhibition. Only one species inhibited fungal growth – Marcgravia nervosa Triana & Planch. Bioassay-guided isolation of this plant resulted in the identification of the active principle as a naphthoquinone, with a minimum inhibitory concentration (MIC) ranging from 85 to 100 μM against Saccharomyces cerevisiae. Similarly, sixty one Q’eqchi’ Maya medicinal plant species were evaluated for their antimicrobial activities. Of these, four species showed more QS inhibition than D. pulchra, seven with comparable biofilm inhibitory activities that of allicin, and two with similarly antifungal activity to berberine. Two spirostanol saponins were isolated from Cestrum schlechtendahlii G.Don, an active antifungal plant. The major saponin showed growth inhibition against Saccharomyces cerevisiae and Fusarium graminearum, with MICs of 16.5 μM and 132 μM, respectively. Further analyses of this compound using chemical genomics suggested that its antifungal mechanism of action is pleiotropic, affecting multiple targets. Taken together, these findings showed that neotropical plants and traditional Q’eqchi’ Maya medicines contain phytochemicals that interfere with bacterial biofilm formation and quorum sensing as well as fungal growth.
Keywords: Quorum sensing; Biofilm; Antifungal; Neotropical plants; Traditional medicine; Q'eqchi' Maya; Bioassay-guided isolation; Saponin; Naphthoquinone